WATER RESOURCES MANAGEMENT - Adlinge S. S.; Dharane S. S; Shashikant Jadhav (International Journal of Innovations in Engineering Research and Technology, 2022)
A comprehensive water resources management is a must for stabilizing, enticing, and revitalizing the agriculture sector. It is a permanent solution to all agriculture sector problems.